Penerapan E-Modul Praktikum Instalasi Penerangan Listrik Untuk Meningkatkan Hasil Belajar Pada Kelas XI TITL Di SMK Negeri 2 Surabaya - Roesita Dekakovi Tauba Setyawan; Achmad Imam Agung; Subuh Isnur Haryudo; Unit Three Kartini (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
The purpose of this study was to determine the practicality, effectiveness and student learning outcomes through the use of the IPL Practicum e-module in class XI TITL at SMK Negeri 2 Surabaya. The novelty of this study is the application of e-modules as new and information technology-based learning tools that contribute to improving student learning outcomes in IPL subjects. The method used is the Pre-Experimental Design in the form of a One-Group Pretest-Posttest Design on a sample of 37 students. Using data analysis techniques includes analysis of practicality, effectiveness as well as, analysis of learning outcomes. In the analysis stage, a needs analysis is carried out aimed at the target of implementation and the pre-test value is obtained, the application is continued to the design stage, adjusting the media to the results of the analysis and several tests are carried out, namely material expert tests, media and language. At the implementation stage, the results of the material expert questionnaire obtained a value of 93%, the media expert questionnaire obtained a value of 83% and, the results of the linguist questionnaire obtained a value of 81%, this means that practical media is used in learning after going through the revision process. The results of the evaluation of learning tools show that the e-module has a significant score of 91% which is categorized as very effective. The pre-test and post-test data on knowledge, skills and attitudes analyzed showed a significance value of zero point zero (0.000) which could mean that there was a significant change in student learning outcomes. Through these results it can be concluded that e-modules are practical and effective in increasing learning outcomes.